PENGUKURAN USER EXPERIENCE PADA E-LEARNING DI LINGKUNGAN UNIVERSITAS MENGGUNAKAN USER EXPERIENCE QUESTIONNARE (UEQ) - Irma Rofni Wulandari; Lilis Dwi Farida (Jurnal Mantik Penusa, 2018)
User experience is the term user in feeling an ease and efficiency in human interaction with computers. The term user experience is increasingly becoming a concern because of the wider and more complex user needs that are not only about functional and aesthetic needs. Human and computer interaction in utilizing information systems has become part of daily activities in student activities, not least in the availability of e-learning. E-learning which functions as a tool in the teaching and learning process does not have an important role in the development of education. E-learning at XYZ University has been used for a long time with users being active lectures and students. The success of an information system can be obtained by analyzing user requirements that are more focused on user experience and comfort. This study was conducted to determine the level of User Experience Questionnare (UEQ) measurement method. The measurement results show the below average level on the attractiveness scale of 0.87, perspiculty of 0.85, efficiency 0.89, dependability of 0.84, and stimulation of 0.84 shows that the five scales are at the below average level, while the novelty scale is at the bad level of 0.29. The measurement results can be used as recommendation for the new user experience design e-learning.